Regulation of site-specific recombination by the C-terminus of λ integrase - Kazmierczak, Robert A. (Oxford University Press, 2002)
Site-specific recombination catalyzed by bacteriophage λ integrase (Int) is essential for establishment and termination of the viral lysogenic life cycle. Int is the archetype of the tyrosine recombinase family whose members are responsible for DNA rearrangement in prokaryotes, eukaryotes and viruses. The mechanism regulating catalytic activity during recombination is incompletely understood. Studies of tyrosine recombinases bound to their target substrates suggest that the C-termini of the proteins are involved in protein–protein contacts that control the timing of DNA cleavage events during recombination. We investigated an Int truncation mutant (W350) that possesses enhanced topoisomerase activity but greater than 100-fold reduced recombination activity. Alanine scanning mutagenesis of the C-terminus indicates that two mutants, W350A and I353A, cannot perform site-specific recombination although their DNA binding, cleavage and ligation activities are at wild-type levels. Two other mutants, R346A and R348A, are deficient solely in the ability to cleave DNA. To explain these results, we have constructed a homology-threaded model of the Int structure using a Cre crystal structure. We propose that residues R346 and R348 are involved in orientation of the catalytic tyrosine that cleaves DNA, whereas W350 and I353 control and make intermolecular contacts with other Int proteins in the higher order recombination structures known as intasomes. These results suggest that Int and the other tyrosine recombinases have evolved regulatory contacts that coordinate site-specific recombination at the C-terminus.